Guidebook on the Development of Climate-Smart Maps and Adaptation Plans (CS-MAP) for Rice Production in Viet Nam - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
The guidebook was officially handed over to the related national offices and local units under the Ministry of Agriculture and Rural Development of Vietnam